The Production of artisanal bamboo furniture: coastal, inclusive and sustainable identity in Ecuador - Cueva KeanChong, Tanya; Franco Zavala, Ana; Ching Chiy, Johnson; Rendón Jaluff, Ivonne Amelia (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This study analyzes the productive, economic and commercial viability of the manufacture of artisanal bamboo furniture in coastal communities of Ecuador, with a focus on its insertion in international markets, particularly in the European Union. The research was developed under a quantitative, non-experimental and projective approach, through the development of a financial model based on production costs, initial investment, income projection and evaluation through indicators such as Net Present Value (NPV) and Internal Rate of Return (IRR). The results show that the production of furniture sets (table and chairs) allows us to increase the added value of the product, reaching annual revenues of $270,000 and a significant net profit. The financial analysis shows a positive NPV and an IRR of more than 50%, confirming the profitability of the project. Likewise, it is identified that bamboo, due to its sustainable properties and cultural value, has high acceptance in European markets oriented to responsible consumption. It is concluded that the implementation of this production model is not only economically viable, but also contributes to local development, environmental sustainability and the international projection of Ecuadorian crafts.